Kondisi Variabel Makro Ekonomi Islam Ditinjau Dari Pengaruh Kebijakan Moneter Studi Kasus : Indonesia Periode Tahun 2010-2014 - Ilmiyah, Bachrotil; Widiastuti, Tika (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study raised the issue of how Islamic macroeconomic conditions in Indonesia is affected by the role of Bank Indonesia. This study aims to determine whether monetary policy implemented BI is able to influence the Islamic macro-economic conditions. Variables used in this study is inflation and profit sharing ratio as variables describing Islamic macroeconomic conditions.The data used in this research is secondary data taken from the official website of Bank Indonesia in the form of time series from January 2010 until December 2014.This study uses eviews 8 to process the data with Based on the results of IRF and statistical analysis showed that the variables of monetary policy and macroeconomic variables Islam shows long-term relationship. From the results of variance decomposition shows that each variable represents a contribution on other variables with a composition of no more than 35%.